2023
DOI: 10.1111/bdi.13336
|View full text |Cite
|
Sign up to set email alerts
|

Common and unique alterations of functional connectivity in major depressive disorder and bipolar disorder

Abstract: Objective Major depressive disorder (MDD) and bipolar disorder (BD) are considered whole‐brain disorders with some common clinical and neurobiological features. It is important to investigate neural mechanisms to distinguish between the two disorders. However, few studies have explored the functional dysconnectivity between the two disorders from the whole brain level. Methods In this study, 117 patients with MDD, 65 patients with BD, and 116 healthy controls completed resting‐state functional magnetic resonan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 86 publications
0
0
0
Order By: Relevance
“…NBS analysis revealed interaction effects within the LN network. In contrast, previous studies reported decreased connectivity within LN networks in adults with MDD [ 25 ]. This disparity could be due to uncontrolled factors such as AOO and medication in previous studies, where adult MDD patients might include both adolescent-onset and adult-onset cases.…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…NBS analysis revealed interaction effects within the LN network. In contrast, previous studies reported decreased connectivity within LN networks in adults with MDD [ 25 ]. This disparity could be due to uncontrolled factors such as AOO and medication in previous studies, where adult MDD patients might include both adolescent-onset and adult-onset cases.…”
Section: Discussioncontrasting
confidence: 59%
“…DPABISurf, an extension of DPABI/DPARSF [ 24 ], was developed by the Institute of Psychology of the Chinese Academy of Sciences and interfaces with the FMRIPprep docker, integrating FreeSurfer, ANTs, FSL, and AFNI for MRI data preprocessing. Further details on MRI data processing are available in our previous research [ 25 ]. Initially, EPI and T1 DICOM data were converted to BIDS format, with the first 10 time points of the EPI data being discarded to eliminate magnetic field instability effects.…”
Section: Methodsmentioning
confidence: 99%